The Family Support Network and Intra-family Relationships as Predictors of Life Satisfaction - Barraza Macías, Arturo (2021)
Objective. The main objective of this paper was to determine the relationship between the elements of family support network and intra-family relationships with life satisfaction. Method. A correlational, cross-sectional, and non-experimental study was carried out with a sample of 314 students from two higher education institutions: 70 men (22.3%) and 244 women (77.7%), with an average age of 27.55 years (SD = 9.57). Results. Results showed that the model constituted by the members of the family support network, the closeness or intimacy among those members, the support shown in intra-family relationships, and the communication excel to predict the vital satisfaction of the individual.